Recent Progress in Lyme Disease and Remaining Challenges - Bobe, Jason R.; Jutras, Brandon L.; Horn, Elizabeth J.; Embers, Monica E.; Bailey, Allison; Moritz, Robert L.; Zhang, Ying; Soloski, Mark J.; Ostfeld, Richard S.; Marconi, Richard T.; Aucott, John; Ma'ayan, Avi; et al. (Frontiers in Medicine, 2021)
Lyme disease (also known as Lyme borreliosis) is the most common vector-borne disease in the United States with an estimated 476,000 cases per year. While historically, the long-term impact of Lyme disease on patients has been controversial, mounting evidence supports the idea that a substantial number of patients experience persistent symptoms following treatment. The research community has largely lacked the necessary funding to properly advance the scientific and clinical understanding of the disease, or to develop and evaluate innovative approaches for prevention, diagnosis, and treatment. Given the many outstanding questions raised into the diagnosis, clinical presentation and treatment of Lyme disease, and the underlying molecular mechanisms that trigger persistent disease, there is an urgent need for more support. This review article summarizes progress over the past 5 years in our understanding of Lyme and tick-borne diseases in the United States and highlights remaining challenges.